Schoolyard rhymes : kids' own rhymes for rope skipping, hand clapping, ball bouncing, and just plain fun - Sierra, Judy.; Sweet, Melissa, 1956- (New York : Alfred A. Knopf : Distributed by Random House, 2005)
Provides a compilation of more than fifty fun, silly, and teasing rhymes commonly heard in playgrounds and at recess.
Includes index.
Maine illustrator.
Keywords: Games; Rhyming games; Singing games